Pengaruh Metode Outbound Terhadap Pembentukan Karakter Kepemimpinan Pada Siswa Kelas V Sekolah Alam Bengawan Solo Tahun Ajaran 2015/2016 - Wijayanto, Satya, Drs. Suwarno, SH., M. Pd (2016)
This research takes the theme of leadership (leadership) cause of the lack of the leader which is ideal for the crisis of character that occurs lately, Bengawan Solo nature school is one of the educational institution that using the leadership curriculum on the learning process trough outbound method. This study aims to know the effects of outbound method trough the formation of the character of leadership on fifth grade students of Bengawan Solo nature school in 2015/2016 academic year. This research is using descriptive quantitative research. Population and sample of the research is the fifth grade student of sekolah alam bengawan solo which consist of 22 students. The instrument of the collecting data is using likert scale, data analysis of the research is the simple linear regression. The result of this research is the outbound method gives an effect trough the formation of character of leadership on fifth grade student of Bengawan Solo nature school 2015 2016 academic year. It is based on the significant test (t test) knows that tcount>ttable, ie 10.677>2.086 and the significant value <0.05, namely 0.000 <0.05. The coefficient of determination (r2) is equal to 0.851, it means that the influence that gives by the outbound method trough the students leadership is of 85.1% while 14.9% is influence by another variable.